The effectiveness of MgCeAl11O19:Tb3+ phosphor in enhancing the luminous efficacy and color quality of multi-chip white LEDs - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Institute of Advanced Engineering and Science, 2020)
In this research paper, we introduced yellow-green MgCeAl11O19:Tb3+ asa new phosphor ingredient to adapt to the quality requirements onthe chromatic homogeneity and emitted luminous flux of modern multi-chip white LED lights (MCW-LEDs). The results from experiments and simulation show that employing MgCeAl11O19:Tb3+ phosphor can lead to much better optical properties and therefore is a perfect supporting material to achieve the goals of the research. When the MgCeAl11O19:Tb3+ phosphor is added into the phosphorus composite which already contains YAG: Ce3+ particles, and the silicone glue, it affects the optical properties significantly. In other words, the concentration of this phosphor can determine the efficiency of lumen output and chromatic homogeneity of WLEDs. In specific, as the concentration of MgCeAl11O19:Tb3+ go up, the luminous yield will increase accordingly, though there is an insignificant decrease in CQS. Moreover, if the MgCeAl11O19:Tb3+ concentration reduce a little bit, it is possible to better the correlated color temperature uniformity and lumen efficacy of LED packages. In addition, the Mie scattering theory, Monte Carlo simulation and LightTools 8.3.2 software are employed to analyze and simulate the LED packages’ structure as well as the phosphor compound.